Understanding the relation between repeat developer interactions and bug resolution times in large open source ecosystems: A multisystem study. Issue 4 (29th November 2020) - Datta, Subhajit; Roychoudhuri, Reshma; Majumder, Subhashis
Abstract: Large‐scale software systems are being increasingly built by distributed teams of developers who interact across geographies and time zones. Ensuring smooth knowledge transfer and the percolation of skills within and across such teams remain key challenges for organizations. Towards addressing this challenge, organizations often grapple with questions around whether and how repeat collaborations between members of a team relate to outcomes of important activities. In the context of this paper, the word 'repeat interaction' does not imply a greater number of interactions; it refers to repeat interaction between a pair of developers who have collaborated before. In this paper, we empirically examine such a question using real‐world data from three diverse development ecosystems, collectively involving 400, 000+ units of work and 600, 000+ comments exchanged between numerous developers. Our statistical models consistently establish a counter‐intuitive relation between repeat developer interaction and bug resolution times. Our experimental results show that more instances of repeat developer interactions over bug fixing are associated with more time taken for the bugs to be fixed. Given the expanse and variety of the underlying data, our results offer an unexpected set of insights on a key dynamic of collaboration in software development ecosystems. We discuss how these insights can influence the practice of large‐scale software development at individual, team and organizational levels. Abstract : In this paper, we empirically examine whether and how repeat collaborations between members of a software development team relate to outcomes of important activities using real‐world data from three diverse development ecosystems, collectively involving 400, 000+ units of work, and 600, 000+ comments exchanged between many developers. Our results consistently establish a counter‐intuitive relation between repeat developer interaction and bug resolution times. The insights from our results can influence the practice of large‐scale software development at individual, team, and organizational levels.